Detection of stress resistance genes in transgenic maize by multiplex and touchdown polymerase chain reaction - Bannikova, M.A. (Вiopolymers and Cell, 2015)
Aim. To develop a methodology for detection of the genes of resistance to the stress factors in transgenic maize by multiplex (mPCR) and touchdown polymerase chain reactions. Methods. isolation of total DNA by CTAB method, purification of DNA from RNA and proteins, electrophoresis of total DNA and amplification products in agarose gel, polymerase chain reaction. Results. The protocol of multiplex and touchdown polymerase chain reactions has been developed for simultaneous verification of the quality of total DNA extracted from the studied maize plant samples and detection of the following genes that determine resistance to the stress factors in the transgenic maize and maize transformation events: BT176, MON810, MON88017, DAS1507, DAS59122, MIR604, GA21, NK603 (mPCR), Bt11, MON863, MON89034, T25 (touchdown PCR). The multiplex PCR and touchdown PCR were developed using the reference samples. Conclusions. The proposed protocol of mPCR and touchdown PCR reactions can be used for mass analysis of maize samples to detect the genes of tolerance/resistance to herbicides and genes of resistance to insects reliably, authentically, quickly and cheaply.